ANALISIS MARGIN OF SAFETY USAHA PETERNAKAN PUYUH â€œMERRYLANDâ€ DI DESA KALI KECAMATAN PINELENG KABUPATN MINAHASA - Wangefela, Lisa; Santa, N M; Salendu, A H.S; Kalangi, L S (ZOOTEC, 2018)
ABSTRACTÂ ANALYSIS OF SAFETYÂ  MARGIN ON â€œMERRYLANDâ€ QUAIL POULTRY FARM AT KALI VILLAGE PINELENG DISTRICT OF MINAHASA REGENCY.Â The purpose of this study was to determine the break-even point of "Merryland" quail poultry farm and to determine the margin of safety of this farm. The research location was at the "Merryland" quail poultry farm on Kali village Pineleng district of Minahasa regency, with the consideration that the venture is a private farm enterprise. This farm enterprise had been operated more than 3 years. The number of birds held were 5000 chicken quail. This study was conducted during one month from December 10, 2016 to January 10, 2017. The method was applied using the case study method, in the form of primary data and secondary data. Primary data were using data obtained from interviews with the respondents through a list of questions that had been provided. Secondary data were obtained using variables at the office related to research data, including the Village Office, District Office, and Office of the Department of Agriculture / Animal Husbandry. Based on the survey, results indicated that quail poultry farm of "Merryland" had reached breakeven sales of 690,732 quail eggs or on sale of IDR259,589,665. If the breeder declined in egg sales, the number of eggs tolerated of farmers not sufferin economic losses were 58.8% of the total sales.Â Keywords : Quail, Margin Of SafetyÂ